Rural Healthcare and Telehealth: The Importance of Social Work Departments at HBCUs in Developing a Competent Workforce in the Rural South - Dawna D. Nelson; Katina Lang-Lindsey (The University of Alabama, 2022)
Telehealth is an emerging area of practice within social work that can potentially have great impacts on the way care is provided to rural communities. Rural communities are racially diverse, older, and tend to have lower incomes resulting in unique barriers to already scarce rural healthcare options. In addition to understanding the logistic differences that may influence healthcare receipt in rural areas, such as transportation and cost, there are additional competencies that are required to effectively implement culturally competent telehealth to rural communities, such as understanding digital inequities. Thus, there is a need for a culturally competent social work workforce to engage with rural communities in order to implement effective telehealth practices. HBCUs are primed to create this workforce as evidenced by their historical contributions to the field and current proximity to marginalized communities. This article will explore rurality and healthcare in the Southern United States, provide a general overview of telehealth use by social workers, and discuss the importance of HBCUs in the role of developing a culturally competent workforce to engage diverse communities and enhance telehealth delivery in rural areas.